Real-Time Intravital Imaging of RGD−Quantum Dot Binding to Luminal Endothelium in Mouse Tumor Neovasculature - Smith, Bryan Ronain; Cheng, Zhen; De, Abhijit; Koh, Ai Leen; Sinclair, Robert; Gambhir, Sanjiv Sam (Nano letters, 2008)
Nanoscale materials have increasingly become subject to intense investigation for use in cancer diagnosis and therapy. However, there is a fundamental dearth in cellular-level understanding of how nanoparticles interact within the tumor environment in living subjects. Adopting quantum dots (qdots) for their excellent brightness, photostability, monodispersity, and fluorescent yield, we link arginine−glycine−aspartic acid (RGD) peptides to target qdots specifically to newly formed/forming blood vessels expressing αvβ3 integrins. Using this model nanoparticle system, we exploit intravital microscopy with subcellular (∼0.5 µm) resolution to directly observe and record, for the first time, the binding of nanoparticle conjugates to tumor blood vessels in living subjects. This generalizable method enabled us to show that in this model qdots do not extravasate and, unexpectedly, that they only bind as aggregates rather than individually. This level of understanding is critical on the path toward ensuring regulatory approval of nanoparticles in humans for disease diagnostics and therapeutics. Equally vital, the work provides a platform by which to design and optimize molecularly targeted nanoparticles including quantum dots for applications in living subjects.